Estación de metro 76 : un recorrido topográfico (2017)
"The Caracas is considered as an avenue that is the limit, generates disconnection and disarticulation at urban level, degrading the city's space. The pedestrian has been forgotten over years as a result of population growth and the city development. However, through this project and with the arrival of the subway in Bogota, what arises is a city where the pedestrian is the main character and everything revolves around it. For this, it is necessary to make a historical path as well as a spatial route to propose different strategies for the city to turn it into a transcendent historically place and at the same time connect it with the pedestrian. It is important to keep in mind that the city and the architecture go hand in hand all the time and for this reason a relationship between these two must be considered." -- Tomado del Formato de Documento de Grado.